PURIFICATION AND COMPARATIVE STUDY OF NGAL ISOFORMS FROM NEUTROPHIL AND KIDNEY ORIGIN SUGGESTS ITS DIFFERENT ROLES UNDER DIFFERENT STRESS CONDITIONS - KUNAL SHUKLA; PARESH BHANUSHALI; ANUJ KUMAR GUPTA; SUSHMA SABHARWAL (International Journal of Pharma and Bio Sciences, 2014)
Neutrophil gelatinase associated lipocalin (NGAL) is a member of the lipocalin family and binds with iron in the presence of enterochelin. The role of NGAL is not clear but earlier experiments suggest that it acts as a bacteriostatic agent and is dramatically up regulated during acute kidney injury (AKI). Immunological studies in the literature have shown that the use of epitope specific antibodies to measure the level of NGAL from AKI patients has significant effects on the performance of the ELISA, CLIA and other assays, due to the expression of different molecular forms of NGAL. To understand the biochemical similarities and differences between NGALs secreted in different diseased conditions, we have purified and characterized NGAL from the urine of AKI patients (kNGAL) and from neutrophils from healthy humans (nNGAL). In our study 2D electrophoresis followed by quantitative analysis were performed to study the differences between the isoforms of kNGAL and nNGAL. Identification of NGALs of both the sources was confirmed by MALDI-TOF/TOF analysis and further validated using ELISA and western blot. The proteomics analysis in our study reveals that kNGAL is slightly acidic and predominantly monomeric in nature; on the other hand, nNGAL is both monomeric and dimeric and ranges from acidic to far basic forms. Further, we also observed a relatively higher extent of sialylation in kNGAL in comparison to nNGAL suggesting the different roles of kNGAL and nNGAL under different diseased conditions.